Report on impact of information technology on education - Boo, Sian San (2008)
A revolution is taking place in education. From the traditional class-based learning to correpondent distance learning to virtual learning, these changes are occurring at an ever-increasing momentum. This report traces the history and development of education in general, as well as in Singapore. The impact of IT on education, too, is discussed in detail.